A novel mechanism of 6-methoxydihydroavicine in suppressing ovarian carcinoma by disrupting mitochondrial homeostasis and triggering ROS/ MAPK mediated apoptosis - Zhang, Huachang; Shangguan, Fugen; Zhang, Lan; Ma, Nengfang; Song, Shuling; Ma, Li; Liu, Chuntong; Liu, Mengke; An, Jing; Li, Hua; Cao, Qizhi (Frontiers in Pharmacology, 2023)
Introduction: Alkaloids derived from M. cordata (Papaveraceae family), have been found to display antineoplastic activity in several types of cancer. However, the antitumor effects and mechanisms of a new alkaloid extracted from the fruits of M. cordata, named 6-Methoxydihydroavicine (6-ME), remains unclear in the case of ovarian cancer (OC). Methods: CCK-8 assay was employed to analyze the cell viabilities of OC cells. RTCA, and colony-formation assays were performed to measure OC cell growth. Alterations in apoptosis and ROS levels were detected by flow cytometry in accordance with the instructions of corresponding assay kits. A Seahorse XFe96 was executed conducted to confirm the effects of 6-ME on cellular bioenergetics. Western blot and q-RT-PCR were conducted to detect alterations in target proteins. The subcutaneous xenografted tumor model of OC was used to further validate the anti-tumor activity of 6-ME in vivo. Results: Here, we reported for the first time that 6-ME inhibits OC cells growth in vitro and in vivo. Meanwhile, we found that 6-ME showed great antineoplastic activities by disrupting mitochondria homeostasis and promoting apoptosis in OC cells. Further investigation of the upstream signaling of apoptosis revealed that 6-ME-triggered apoptosis was induced by reactive oxygen species (ROS)-mediated mitogen-activated protein kinase (MAPK) activation and mitochondria dysfunction in OC cells. Furthermore, we found oxaloacetic acid (OAA), a crucial metabolite has been proved to be related to NADPH production, can block the cytotoxicity and accumulation of ROS caused by 6-ME in OC cells. Discussion: In summary, our data show that 6-ME exhibits cytotoxicity to OC cells in a ROS-dependent manner by interrupting mitochondrial respiration homeostasis and inducing MAPK-mediated apoptosis. This evidence suggests that 6-ME is a promising remedy for OC intervention.